Masyarakat Desa dan Budayanya : Studi Kasus Budaya Aron dan Kerja Tahun Ngerires di Desa Batukarang Kecamatan Payung - Pristi Suhendro Lukitoyo; Salsa Bila Lubis; Nadilla Andrina; Indah Permata Sari; Bornok Hotmatua Situmeang (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
Village communities generally have a cultural system deeply rooted in traditional values passed down through generations. This system encompasses various aspects of life, including agriculture, which is the primary source of livelihood. In Batukarang Village, Payung District, Karo Regency, North Sumatra, local agricultural culture is reflected in two key practices that remain preserved to this day: the aron tradition and kerja tahun (year work). These traditions not only demonstrate how the community carries out agrarian-based economic activities but also demonstrate how social, spiritual, and cultural elements are interwoven within Karo agricultural practices. Aron is a local term referring to small groups or communities that assist each other in farming activities. This system serves as a form of mutual cooperation that strengthens solidarity among residents. In practice, aron groups typically work in rotation on other group members' fields. In addition to speeding up the work process, this system also strengthens social bonds and fosters a sense of togetherness within village life.